How can there be an ecological transition without a just transition? – starting with the European Union - Machado, Nataly (UNIO – EU Law Journal, 2023)
Understanding that the nations and nation states that have historically contributed the least to climate change suffer the most from its impacts and have fewer opportunities to protect themselves or adapt to them is the first step in the process of understanding the importance of a just and inclusive transition for all. In an immense diversity of realities, this very notion is no different in the context of the European Union. This article seeks to show the need to find concrete tools, through the European Union’s protagonism, for an ecological transition with social justice.